Harnessing Nuclear Energy to Gold Nanoparticles for the Concurrent Chemoradiotherapy of Glioblastoma - Jui-Ping Li; Yu-Cheng Kuo; Wei-Neng Liao; Ya-Ting Yang; Sih-Yu Chen; Yu-Ting Chien; Kuo-Hung Wu; Mei-Ya Wang; Fong-In Chou; Mo-Hsiung Yang; Dueng-Yuan Hueng; Chung-Shi Yang; et al. (Nanomaterials, 2023)
Nuclear fission reactions can release massive amounts of energy accompanied by neutrons and γ photons, which create a mixed radiation field and enable a series of reactions in nuclear reactors. This study demonstrates a one-pot/one-step approach to synthesizing radioactive gold nanoparticles (RGNP) without using radioactive precursors and reducing agents. Trivalent gold ions are reduced into gold nanoparticles (8.6–146 nm), and a particular portion of 197Au atoms is simultaneously converted to 198Au atoms, rendering the nanoparticles radioactive. We suggest that harnessing nuclear energy to gold nanoparticles is feasible in the interests of advancing nanotechnology for cancer therapy. A combination of RGNP applied through convection-enhanced delivery (CED) and temozolomide (TMZ) through oral administration demonstrates the synergistic effect in treating glioblastoma-bearing mice. The mean survival for RGNP/TMZ treatment was 68.9 ± 9.7 days compared to that for standalone RGNP (38.4 ± 2.2 days) or TMZ (42.8 ± 2.5 days) therapies. Based on the verification of bioluminescence images, positron emission tomography, and immunohistochemistry inspection, the combination treatment can inhibit the proliferation of glioblastoma, highlighting the niche of concurrent chemoradiotherapy (CCRT) attributed to RGNP and TMZ.